Sudden Heart Rate Reduction Upon Optogenetic Release of Acetylcholine From Cardiac Parasympathetic Neurons in Perfused Hearts - Moreno, Angel; Endicott, Kendal; Skancke, Matthew; Dwyer, Mary Kate; Brennan, Jaclyn; Efimov, Igor R.; Trachiotis, Gregory; Mendelowitz, David; Kay, Matthew W. (Frontiers in Physiology, 2019)
The balance of sympathetic and parasympathetic tone provides exquisite control of heart rate and contractility and has also been shown to modulate coronary flow and inflammation. Understanding how autonomic balance is altered by cardiac disease is an active area of research and developing new ways to control this balance is providing insights into disease therapies. However, achieving acute neuron-specific stimulation of autonomic neurons can be difficult in experiments that measure the acute effects of nerve stimulation on the heart. Conventional electrical and pharmacological approaches can be spatially and temporally non-selective. Cell-specific expression of light-activated channels (channelrhodopsin, ChR2) is a powerful approach that enables control of the timing and distribution of cellular stimulation using light. We present such an optogenetic approach where parasympathetic cardiac neurons are selectively photoactivated at high temporal precision to initiate cholinergic-mediated slowing of heart rate. Mice were crossbred to express ChR2 in peripheral cholinergic neurons using Cre-Lox recombination driven by a choline acetyltransferase (ChAT) promoter. Hearts from adult mice were excised, perfused, and the epicardium was illuminated (peak 460-465nm) to photoactivate ChR2. In one set of studies, hearts were illuminated using a large-field LED light source. In other studies, a micro LED was placed on the right atrium to selectively illuminate the junction of the superior vena cava and right atrium. The ECG was acquired before, during, and after tissue illumination to measure changes in heart rate. Upon illumination, hearts exhibited sudden and dramatic reductions in heart rate with restoration of normal heart rate after cessation of illumination. Delays in atrioventricular conduction were also observed. Heart rate reductions at the highest irradiance levels were similar to heart rate reductions caused by application of bethanechol (10µM) or acetylcholine (800µM). Atropine (50nM) completely blocked the effect of ChR2 photoactivation, confirming cholinergic mediation. Optogenetic activation of intrinsic parasympathetic neurons reduced heart rate in an immediate, dose-dependent fashion, resembling the slowing of sinus rate in response to acetylcholine. Our results demonstrate a new approach for controlling parasympathetic modulation of cardiac function by selectively activating the endogenous release of acetylcholine from intrinsic cardiac cholinergic neurons.